Pengenalan Dasar-dasar Komputer untuk Tingkat SD dan SMP sebagai Upaya Meningkatkan Kualitas Pembelajaran Komputer - Fayun Indiyana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
The discovery of computers had an impact on the field of education. Some of these impacts are positive or beneficial, but there are also negative or detrimental ones. In the field of education, computers are used as a learning tool. This means that computers are used to help teachers and students in the learning process. For example, computers are used to do assignments, type assignments, search for learning materials on the internet, and so on. Apart from that, another impact of computers in the field of education is the ease of the teaching and learning process. The existence of computers makes it easier for teachers to explain material, for example through multimedia, such as animation, video, and others. The aim of this community service activity is to introduce the basics of computers for elementary and middle school levels in an effort to improve the quality of computer learning. All activities carried out have been adapted to the needs of the community, both from village heads and hamlet heads, even those who receive the learning, namely elementary and middle school children in Pandan Wangi Village, Jerowaru District, East Lombok Regency. The activity began with discussions and consultations with village officials, then continued with outreach to several schools. This service activity was successful in all the programs that had been planned. Activities that have been carried out include: 1) how to turn it off and on (sleep, shutdown and restart) as well as introducing keyboard functions on a laptop and hands-on practice; 2) introduce and explain the function of Ms. Word, Ms. Excel, and power point as well as direct practice; and 3) evaluation. Based on the description of this activity, it can be concluded that the focus of this service activity is to increase children's interest and awareness in learning the basics of computers as demonstrated by the successful initial planning for the implementation of the activity.